Recreation value of domestic visitors in Kilim Karst Geoforest Park, Langkawi, Malaysia - Zameli, Nurul Hikmah (2014)
Geopark is known as a national protected area that has geological unique features that are of particular significance, rarity, or aesthetic appeal. The concept of Geopark is an integrated concept of protection, education, and sustainable development of a natural area. There are resources for recreational activities in Geoparks that evolve as a tourism development and attract tourists to visit Geoparks. Tourists gain benefits or satisfaction through their experiences while visiting Geoparks. These benefits are subjective to each person; however, it can be quantified by applying economic approaches to give value to the heritage sites. This study puts forward the concept in valuing the Geopark in Kilim, Langkawi. Kilim Karst Langkawi Geopark (KKGP) consists of the oldest limestone hills with a variety of shapes and sizes of pinnacles and unique flora and fauna in the mangrove forest and at the river and beach. The main objective of this study is to assess the economic value of KKGP. This main objective is followed by three specific objectives, which are to 1) to determine the social demography of domestic visitors visiting KKGP, 2) to determine the factors influencing visitors to visit KKGP, and 3) to determine the consumer surplus. Individual Travel Cost Method (ITCM) was employed to estimate the benefits to the visitors of KKGP. A total of 300 of respondents among domestic tourists in KKGP were surveyed using a structured questionnaire. The distribution of questionnaire was conducted in area of KKGP only to ensure the visitors had already experienced the recreational activities around the area. The questionnaire was designed to attain information such as socioeconomic information of the visitors (e.g., gender, education, age,monthly income), trip characteristics of visitors (perception towards important of KKGP, perception towards facilities and services in KKGP, perception towards surrounding environment KKGP, perception towards crowdedness in KKGP), and all travel cost of visitors (e.g., travel cost, time cost, on-site cost, alternative cost). The count data from the variables in this study were modelled by employing linear regression. The findings showed that there were more female tourists (56%) than male tourists (34%). Most of the tourists were in the range of 41–55 years old (29.3%). The highest (34.6%) percentage of tourists was having diploma/professional certificate. Service-related work was found to be the highest (24.1%) in terms of type of profession. 13 independent variables were used in the multiple regression model to determine the factors influencing visitation to KKGP. Only five factors were found to be significant at 5% level, namely travel cost to KKGP, education years of tourists, cost of travelling time, monthly income, and visitors’ perception towards importance of Geopark. The consumer surplus was estimated at RM 46,202.43 per year at zero cost. The estimated average consumer surplus was RM 310/trip/year. Thus, the economic value for KKGP was estimated approximately at RM 47 million for 2011. The recreational value found in this study showed that the recreational activities in KKGP offered benefits to the visitors. This study provides information regarding the value of satisfaction gained by the tourists during their visit to KKGP. This information may help the management in decision making process to offer good services and products in future.